Skip to main content

All Questions

-2 votes
2 answers
62 views

How to form a CNF of following formula [closed]

We got an exercise to make a CNF out of the following formula: $$G = ((A \vee \neg B \vee C) \wedge (C \vee D)) \vee ((A \vee \neg C) \wedge (B \wedge D))$$ I've tried to make an equivalent equation ...
Maxim Glazunov's user avatar
0 votes
1 answer
280 views

How to get CNF of propositional formula form DNF of its complement?

Explain how to read off a CNF for propositional formula directly from a DNF from its complement. I've managed to explain it in words, but can't write a rigorous proof of that. How to show this in ...
user avatar
0 votes
1 answer
66 views

DNF to CNF of a simple expression

I have a formula like this: $$\bigvee_{\substack{i \in [1,...,m] \\ j \in [1,...,m]}} x_{i} \wedge x_{j}$$ What is the equivalent formula in CNF (conjunctive normal form)?
mrjamaisvu's user avatar
1 vote
1 answer
76 views

CNF formula for manipulating words

I am trying to create CNF formula for manipulation of a word. word is a sequence of letters from a $\Sigma$ alphabet. A word is encoded by variables like $x_{i,a}$ which means that the letter $a$ is ...
mrjamaisvu's user avatar
0 votes
1 answer
55 views

CNF for modilisation of a word

Imagine that we are interested in problem of words. A word is a sequence of letters from a $\Sigma$ alphabet. For encoding a word in SAT we are using variable like $x_{i,a}$ which means that in ...
mrjamaisvu's user avatar
2 votes
0 answers
253 views

How can I find the CNF of ($A$ and $B$ or $C$) and ($B$ or not $C$) using a Karnaugh map?

$$(A\land B \lor C) \land (B \lor \lnot C)$$ I know how to create the truth table and Karnaugh map of a logic expression. But I couldn't find exactly how to calculate the simplified CNF of it using ...
babak abdzadeh's user avatar
2 votes
1 answer
799 views

CNF and DNF form of single logical variable

I am learning boolean algebra. So apologies for this naive question. During our discussion among friends, we came across following puzzle, How can I convert following statement into CNF and DNF? $$ ...
Dexter's user avatar
  • 123
0 votes
1 answer
665 views

Converting to DNF from CNF

I'm having a bit of a problem when trying to convert this CNF formula to DNF: \begin{align} & \left(a_1 \vee \neg a_2 \vee \neg a_3 \vee ... \vee \neg a_K \right) \wedge \\ & \left(\neg a_1 \...
Gogol31's user avatar
0 votes
1 answer
163 views

conjunctive normal form distribution over logical or?

when converting to CNF do you have to distribute ors over ors ex. (A or B) or C, or can you leave it just like that I am wondering because I have to convert a bunch of first order logic to clausal ...
JRowan's user avatar
  • 381
1 vote
0 answers
1k views

A reduction of 3-CNF down to 2-CNF for boolean satisfiability

Could you please review the following candidate solution for the boolean satisfiability problem? It is known that 2-CNF has a polynomial solution. Now consider we have a 3-CNF (AFAIK, it's proven ...
Serge Rogatch's user avatar
1 vote
1 answer
150 views

Boolean algebra - Converting DNF form to CNF form

I´ve tried at least dozen ways to convert DNF to CNF, yet I always end up with something wrong. Here is the DNF: (B ∧ D) ∨ (C ∧ D) ∨ (¬D ∧ ¬B) ∨ (¬D ∧ ¬C) . Is there someone who can help me with it ...
AlZiSVK's user avatar
  • 21
2 votes
1 answer
606 views

Boolean algebra - Converting DNF form to CNF

I've tried at least a dozen ways to convert this DNF to CNF, yet I always end up with something unusable. Here is the DNF: $$y= (A \wedge B \wedge \neg C \wedge D) \vee (A \wedge B \wedge C \wedge \...
Andrej Šereš's user avatar
0 votes
2 answers
345 views

DNF and CNF look the same?

When constructing both a DNF and CNF of the below, my solutions look the same. I must be off somewhere. This is what they look like: $\lnot s ∨ \lnot q ∨ \lnot s$ How would you construct a DNF and ...
logicsnewbie2019's user avatar
4 votes
1 answer
5k views

Tseytin transformation example

I am trying to understand Tseytin transformation and I can't really find any reliable info on the internet. I pretty much understand the steps until I get to the point I have to convert all ...
Pastrami's user avatar
2 votes
2 answers
1k views

Is it ok this CNF of a Boolean function?

I have to find out the CNF of $$\begin{matrix} f(x,y,z)&=&(x\wedge y)\vee(x\wedge z),\end{matrix}$$ where $f$ is a Boolean function. $$\begin{matrix}&f(x,y,z)&=&(x\wedge y)\vee(x\...
manooooh's user avatar
  • 2,269

15 30 50 per page